Pengaruh Kepemimpinan Terhadap Motivasi Kerja Karyawan Airport Operation Landside & Terminal (AOLT) di PT Angkasa Pura I Bandar Udara Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Melisa Yolanda Evrillya. S; Yunus Purnama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Foreign Object Debris or FOD is a foreign object that has the potential to pose a hazard to Effective leadership plays a pivotal role in motivating employees to perform optimally within an organization. Leaders who are creative and innovative can significantly influence their subordinates to achieve organizational objectives, as well as provide motivation that encourages active participation. Work motivation refers to the internal drive that influences an individual's effort, persistence, and determination in completing tasks. The purpose of this study is to examine the impact of leadership on the work motivation of employees at the Airport Operation Landside & Terminal (AOLT) division of PT Angkasa Pura I Sultan Aji Muhammad Sulaiman Sepinggan Airport in Balikpapan. This research was conducted from August 1 to December 19, 2024, using a quantitative approach. The population of this study consisted of 30 employees from AOLT, selected through non-probability sampling. The data collected were analyzed using SPSS software, applying simple linear regression analysis, T-tests, and coefficient of determination tests. The findings indicate that leadership has a significant effect on employee work motivation. This is supported by a significance value of 0.000, which is less than 0.05, suggesting a positive impact. The magnitude of leadership's influence on work motivation is further demonstrated by a coefficient of determination (R²) value of 58.3%, which reflects the extent to which leadership contributes to enhancing employee work motivation.